Research of the intellectual component of first-graders' adaptation to education as an indicator of the effectiveness of implementation of the principles of New Ukrainian School in the educational process (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the analysis of the problem ofadaptation of today’s first-graders to study at school. The author pays attentionto the disclosure of the specifics of adaptation of first-graders to study underconditions of implementation of the principles of New Ukrainian School, inparticular the program "On the Wings of Success". The paper presents theresults of the empirical study of the intellectual component of first-graders'adaptation to learning. The results of the comparative analysis of diagnosticsresults of the level of formation of the intellectual component of adaptation offirst-graders studying under the program "On the wings of success" and underconditions of traditional education have been presented.
Keywords: Adaptation; adaptation of first-graders to study; structural components of adaptation; intellectual component of adaptation to training; educational program